The Role of Inspection and Testing Technologies in Food Quality Management - Di Yang (International Journal of Public Health and Medical Research, 2026)
Food safety concerns the national economy and people's livelihood. Inspection and testing technologies serve as the core technical support for ensuring food quality and achieving scientific supervision. Based on the practical needs of food quality management, this paper systematically analyzes the core roles of inspection and testing technologies in food quality management, including improving food quality, optimizing process control, strengthening risk early warning, regulating market order, and promoting industrial upgrading. It also proposes optimization strategies to address the current limitations of these technologies, aiming to provide a theoretical reference for the scientific advancement of food quality management.